A therapeutic role for targeting c-Myc/Hif-1- dependent signaling pathways - Podar, Klaus; Anderson, Kenneth C. (Cell cycle, 2010)
Deregulated c-Myc occurs in 30% of human cancers. Similarly, hypoxia- inducible factor (HIF) is commonly overexpressed in a variety of human malignancies. Under physiologic conditions, HIF inhibits c-Myc activity; however, when deregulated oncogenic c-Myc collaborates with HIF in inducing the expression of VEGF, PDK1, and hexokinase 2. Most of the knowledge of HIF derives from studies investigating a role of HIF under hypoxic conditions, however, HIF-1α stabilization is also found in normoxic conditions. Specifically, under hypoxic conditions Hif-1- mediated regulation of oncogenic c-Myc plays a pivotal role in conferring metabolic advantages to tumor cells as well as adaptation to the tumorigenic micromilieu. In addition, our own results show that under normoxic conditions oncogenic c-Myc is required for constitutive high Hif-1 protein levels and activity in Multiple Myeloma (MM) cells thereby influencing VEGF secretion and angiogenic activity within the bone marrow microenvironment. Further studies are needed to delineate the functional relevance of HIF, MYC, and the HIF-MYC collaboration in MM and other malignancies, also integrating the tumor microenvironment and the cellular context. Importantly, first studies already demonstrate promising preclinical results of novel agents, predominantly small molecules, which target c-Myc, HIF or both.
Gesehen am 04.05.2023